Recycled natural wastes in metakaolin based porous geopolymers for insulating applications. (September 2015) - NGouloure, Zénabou N.M.; Nait-Ali, Benoît; Zekeng, S.; Kamseu, E.; Melo, U.C.; Smith, D.; Leonelli, C.
Abstract: The effectiveness of two amorphous silica based wastes, rice husk ash and volcanic ash powders, used to act as structural reinforcement and partial replacement of metakaolin in porous matrices for thermal isolation was assessed. Both wastes produced colloidal phase that contributed to improve the reactivity and homogeneity of the matrices enhancing the mechanical strength. Rounded pores were obtained in relation with significant reduction of the interpore partitions under controlled addition of the blowing agent. The bulk thermal conductivity decreased from 0.6 to less than 0.15 W m −1  K −1 with the increase of the concentration of blowing agent. The final matrix presented pore size distribution and pore connectivity that allows analytical description and prediction of their effective thermal conductivity.Results demonstrated that clear relations can be established among the viscosity of the pastes, chemical composition, amount of blowing agent and the volume expansion/pore size distribution. Highlights: Rice husk ash and volcanic ashes are used as replacement for metakaolin for the development of porous building lightweight composites. Controlled addition of blowing agent leads to good structural porous network with improved thermal insulation. Rounded pores were obtained with significant reduction of the interpore partitions. The optimization of the microstructure reduced the important component of heat transfer in insulating materials which is the heat transfer by conduction.